Effect of Microstructural Evolution on Mechanical Properties and Fracture Modes of AlSi10Mg Blocks Fabricated by Selective Laser Melting after Stress Relief Annealing. Issue 12 (14th September 2022) - Li, Jianzhu; Li, Yujie; Wang, Zhe; Li, Changguang; Yuan, Hai; Hao, Yun
Abstract : AlSi10Mg parts fabricated by selective laser melting (SLM) are frequently reported to have heterogeneous microstructures. How this affects the mechanical properties of SLM parts still requires further study. Herein, AlSi10Mg blocks with simple cuboid shape are printed and annealed at 300 °C. Their microstructure changes significantly from edge to center and from top to bottom. Low‐temperature annealing is not sufficient to eliminate structural heterogeneity. Before annealing, the Si‐rich phase is fine and mainly exists in the form of a eutectic network. The as‐printed blocks have high tensile strength, and the fracture surface exhibits a mix of transcellular pits and pores. After annealing, the network structure is completely broken or disappeared in most locations in the blocks. The Si‐rich phase is significantly coarsened and even segregated locally along the melt pool boundaries. Yield strength is reduced by 25%–47%, but elongation values are doubled. Tensile samples are fractured by an along‐the‐pool boundary fracture mode along the boundary. Micropores formed during the printing process are aggregated in the about 200 μm thick outer surface layer of the block. They also have a significant effect on the local elongation both before and after annealing. Abstract : The microstructure and tensile properties of selective laser melting (SLM) AlSi10Mg blocks before and after stress‐relief annealing are studied and compared. The results demonstrate that pores and the Si‐rich phase have significant effects on the local tensile properties, especially elongation. The as‐printed samples fracture by a transcellular fracture mode while the annealed one by an along‐the‐pool boundary fracture mode.